The Effect of Halal Assurance, Product Quality and Social Media Reviews on Attitudes and Interest in Buying Food for Muslim Consumers in Yogyakarta Restaurants - Cahyani, Andini Septiara; Sumadi (CV. Lenggogeni Data Publishing, 2023)
This study aims to analyze and explain the influence of halal guarantees, product quality, and social media reviews on attitudes and food purchase intention for Muslim consumers at restaurants in the Yogyakarta area. This study uses primary data using convenience sampling techniques with samples obtained from 200 Muslim consumer respondents. This study uses the Structural Equation Modeling (SEM) analysis method with data processing using the SmartPLS version 3.0 program. The results of this study show that halal guarantees, product quality, and social media reviews have a positive and significant effect on Muslim consumers' purchase intention. The consumer attitudes that are influenced by halal guarantees, product quality, and social media reviews show positive and significant results. Furthermore, consumer attitudes also show a positive and significant influence on purchase intention. , ,,